Recurrent epigenetic silencing of the PTPRD tumor suppressor in laryngeal squamous cell carcinoma. Issue 3 (February 2017) - Szaumkessel, Marcin; Wojciechowska, Sonia; Janiszewska, Joanna; Zemke, Natalia; Byzia, Ewa; Kiwerska, Katarzyna; Kostrzewska-Poczekaj, Magdalena; Ustaszewski, Adam; Jarmuz-Szymczak, Malgorzata; Grenman, Reidar; Wierzbicka, Malgorzata; Bartochowska, Anna; et al.
Cellular processes like differentiation, mitotic cycle, and cell growth are regulated by tyrosine kinases with known oncogenic potential and tyrosine phosphatases that downmodulate the first. Therefore, tyrosine phosphatases are recurrent targets of gene alterations in human carcinomas. We and others suggested recently a tumor suppressor function of the PTPRD tyrosine phosphatase and reported homozygous deletions of the PTPRD locus in laryngeal squamous cell carcinoma. In this study, we investigated other gene-inactivating mechanisms potentially targeting PTPRD, including loss-of-function mutations and also epigenetic alterations like promoter DNA hypermethylation. We sequenced the PTPRD gene in eight laryngeal squamous cell carcinoma cell lines but did not identify any inactivating mutations. In contrast, by bisulfite pyrosequencing of the gene promoter region, we identified significantly higher levels of methylation (p = 0.001 and p = 0.0002, respectively) in 9/14 (64%) laryngeal squamous cell carcinoma cell lines and 37/79 (47%) of primary laryngeal squamous cell carcinoma tumors as compared to normal epithelium of the upper aerodigestive tract. There was also a strong correlation (p = 0.0001) between methylation and transcriptional silencing for the PTPRD gene observed in a cohort of 497 head and neck tumors from The Cancer Genome Atlas dataset suggesting that DNA methylation is the main mechanism of PTPRD silencing in these tumors. In summary, our data provide further evidence of the high incidence of PTPRD inactivation in laryngeal squamous cell carcinoma. We suggest that deletions and loss-of-function mutations are responsible for PTPRD loss only in a fraction of cases, whereas DNA methylation is the dominating mechanism of PTPRD inactivation.